Directionally Solidified Al-Cu-Si-Fe Quaternary Eutectic Alloys - Buyuk, U.; Engin, S.; Kaya, H.; Cadirli, E.; Marasli, N. (PLEIADES PUBLISHING LTD, 2020)
Directional solidification of eutectic alloys attracts considerable attention because of microhardness, tensile strength, and electrical resistivity affected by eutectic structures. In this research, solidification processing of Al-Cu-Si-Fe (Al-26 wt % Cu-6.5 wt % Si-0.5 wt % Fe) quaternary eutectic alloy by directional solidification is examined. The alloy was prepared by vacuum furnace and directionally solidified in Bridgman-type equipment. During the directional solidification process, the growth rates utilized varied from 8.25 to 164.80 mu m/s. The Al-Cu-Si-Fe system showed a eutectic transformation, which resulted in the matrix Al, lamellar Al2Cu, plate Si, and plate Al7Cu2Fe phases. The eutectic spacing lambda(Al2Cu) between lamellae of Al2Cu, as well as-lambda (Si), between plates of Si phase,-was measured. Additionally, the microhardness, tensile strength, and electrical resistivity of the studied alloy were determined using directionally solidified samples, and the experimental relationships between them were obtained. It was found that the microhardness, tensile strength, and electrical resistivity were affected by both eutectic spacing and the growth rate.
Keywords: quaternary Al-based alloy; microstructure; tensile strength; microhardness; electrical resistivity; ELECTRICAL CHARACTERIZATION; MECHANICAL-PROPERTIES; Metallurgy & Metallurgical Engineering